Temporary Work as an Active Labor Market Policy: Evaluating an Innovative Activation Program for Disadvantaged Youths - Christoph R. Ehlert; Jochen Kluve; Sandra Schaffner (Economics Bulletin, 2012)
While high rates of youth unemployment are a severe problem in most European countries, the program evaluation literature shows that di sadvantaged youths constitute a group that is particularly difficult to assist effectively. As innovative measures are thus needed, we evaluate a German pilot program that ta rgets low-skilled young unemployed and combines three components: a) individual coaching, b) classroom training and c) temporary work. Using an ex-post quasi-randomization approach, our analysis shows that the program has a positive impact on the post-program employment probability of participants.
Keywords: J0; J6; 330; program evaluation; disadvantaged youths; temporary work; ALMP